Interpreting the Witness: Frederick Thomas Morrison and Other Accounts of Precolonial Lake Nyasa, 1878 to 1891 - Morrison, Christopher James Hamilton (Stellenbosch : Stellenbosch University, 2026)
Thesis (MA)--Stellenbosch University, 2026.